PARADIGMA PUSTAKAWAN TERHADAP LAYANAN REFERENSI DI UPT PERPUSTAKAAN UNIVERSITAS ANDALAS - Amanda, Fiya; Nabila, Jeihan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research discusses the librarian's paradigm of reference services at the Andalas University Library. The purpose of this study was to describe the librarian's paradigm of reference services at the Andalas University Library. This research uses a qualitative approach with descriptive methods. Data collection techniques by means of semi-structured interviews. Interviews were conducted with three informants who were selected by purposive sampling technique. The results showed that the ability of the University Library reference librarian using the RUSA theory (2003). Some librarians have fulfilled the five RUSA competencies and some have not mastered them, namely the competencies of access, knowledge base, promotion, collaboration, and evaluation. For this reason, librarians are expected to learn things related to current library developments.Keywords: Librarian Paradigm, Reference Services, Librarian Competence.